Pengenalan dan Pemilahan Botol Kosong pada Reverse Vending Machine menggunakan metode Euclidean Distance - Aulia el Hakim; Ardian Prima Atmaja; Joko Hartadi; Ahmad Wildan Muammar (Politeknik Negeri Cilacap, 2020)
Reverse Vending Machine is a machine where users will get a reward in the form of a deposit of money from collecting empty bottles. The Recognition and sorting of bottles currently done by several methods including the Recognition of materials using IR spectrometers, identification of bottles according to the barcode attached to the bottles, and using Image Processing technology to detect the shape of the bottles. In this study, the Recognition and sorting of empty bottles were carried out using three sensors. The Inductive Proximity sensor is used to detect metal or nonmetal bottles, the Loadcell sensor is used to calculate the weight of the bottle, and the LDR is used to detect the colour of the bottle based on the light intensity received by the LDR sensor. From tests conducted using the Euclidean Distance algorithm, it can be seen that Reverse Vending Machine can detect and sort the type of bottle waste based on 3 parameters namely weight, metal value, and colour of the bottle in real-time and can provide reward points to users according to bottle criteria.